Informal institutions and managers’ earnings management choices: Evidence from IFRS-adopting countries - Hussein Halabi (Journal of Contemporary Accounting & Economics, 2019)
In this study, we investigate the role of informal institutions (religiosity and culture) in determining managers’ choices ofearnings management methods (accruals vs. real activities), after controlling for formal institutions (investor protection,enforcement quality and equity market development). Using an ethical perspective, we find that managers tend to choose anearnings management strategy that meets the prevailing social (informal) norms of the environment where the firm isheadquartered. Specifically, our analysis shows that firms domiciled in countries with strong religious adherence and highpower-distance cultures prefer to manage their earnings ‘upwards’ through real activities rather than accruals. Overall, ourresults suggest that informal institutions determine managers’ earnings management choices at least as strongly as formalinstitutions do. It would therefore be misleading to analyze managers’ choices in managing earnings solely from the formalrules perspective without considering the role of informal constraints or vice versa.